Intervention at the level of the firm: employer-sponsored training and wage growth in post-unification Germany - Georgellis, Y.; Lange, Thomas (Emerald Group Publishing Ltd, 2007)
Purpose – The aim of the paper is to assess the determinants and impact of employer sponsored further training on wage growth in West Germany over the period 1992 to 2002. Design/methodology/approach – Following a descriptive narrative on further training and wages in Germany, data derived from the West German sub-sample of the German Socio-Economic Panel is being utilised, which has the main advantage of providing detailed information about the respondents' labour market histories prior to and after 1992. The information provides powerful predictors, controlling for the endogeneity of the training participation decision when estimating a wage growth equation. To assess the impact of training on wages, Heckman selectivity corrected wage equations are used, with the selection being based on a probit model for the probability that an individual receives firm-sponsored training. Findings – The analysis provides details of significant gender differences in both, the incidence and earnings impact of further training. The results show that further training has a strong positive effect on wages. However, gender inequality issues remain a salient feature of the German training system, which further training only reinforces. The analysis also suggests that the economic conditions during Germany's post-unification period may have mitigated some of the potential benefits of further training on wage growth. Originality/value – Despite its growing importance, the determinants and earnings impact of employer sponsored, further training have attracted little attention in the empirical literature. Even less is known about the impact of further training during Germany's post‐unification period. This paper adds value by contributing to this fledgling field of investigation.